Association of female sexual hormones with QTc time in hypertensive subjects. (14th October 2021) - Grubler, M; Verheyen, N.D; Meinitzer, A; Tascharre, M; Fiedler, L; Roithinger, F.X; Maerz, W; Tomaschitz, A; Pilz, S
Abstract: Background/Introduction: The rate corrected QT time (QTc) is the most commonly used ECG derived parameter to identify and risk-stratify inherited and acquired arrhythmia risk. Among the many potentially influencing factors, the female menstrual cycle has been described to lead to minor intra-individual changes, but the overall influence of sexual hormones on the QTc is incompletely understood. We therefore aimed to elucidate this relationship in hypertensive subjects. Purpose: To identify confounding factors in QTc determination and elucidate potential endocrine causes of variable QTc time. Methods: The Styrian Hypertension study is a cohort study aiming to identify novel cardiovascular risk factors. Subjects were recruited from a tertiary care center outpatient clinic. QTc was calculated according to Framingham and linear regression formulas adhering to the AHA/ACCF/HRS 2009 guideline for surface ECG interpretation. Plasma concentrations of estrone (E1), estradiol (E2), 17α-Hydroxyprogesterone and progesterone were measured by Biocrates AbsoluteIDQ Stero17 Kit. Patients on QTc altering medication were excluded from the present analyses. Results: A total of 142 participants (mean [SD] age, 59.4 [11.7] years; 52% women, 80, 1% post-menopause) were eligible for the present analyses. Linear regression analyses adjusted for potassium, HbA1c, NTproBNP and mean systolic blood pressure revealed only an association of QTc with progesterone (beta coefficient [95% CI]) of 0.38 [0.14 – 0.62] (P=0.002) in males. Detailed analyses revealed an U-shaped association. The other hormones showed no significant association in the present cohort of patients. Subgroups of premenopausal women and of patients without elevated blood pressure revealed no statistically significant results. Conclusions: Contrary to previous evidence we found no sign. association between female sexual hormones and QTc time. We observed increased QTc time in males depending on their progesterone plasma concentrations, but the isolated finding may be a statistical outlier. Funding Acknowledgement: Type of funding sources: None.